Evaluation Of Outcomes of Iraqi Medical Students' Engagement in The Community Through Project-Based Learning Approach: Abstract - العامري, علي منصور جاسم; Al Ameri , Ali Mansoor (Karbala Journal of Medicine, 2024)
Purpose: In most medical faculties in Iraq, scientific research is introduced late in the curriculum. Studies exhibit that the scientific engagement of medical college students can be fostered through the early introduction of the project-based learning (PtBL) strategy in the medical curriculum. To be started, PtBL approach in this study considers gestational diabetes and gestational hypertension as research areas. However, the medical education literature does not show the short-term and intermediate-term outcomes of PtBL, including those related to research projects findings. Aims and objectives: The project aimed to explore the short and intermediate-term outcomes of the PtBL approach in improving the academic knowledge and skills of medical students at the College of Medicine, University of Kerbala to aid achieving institutional mission. Methods: A mixed-method study was designed to assess the short and intermediate-term outcomes of PtBL in medical education. The project started after assessing stakeholders' needs. This was done by analyzing a needs assessment form which was answered by 83 persons, including students, faculty members, and other health care providers. The approval to conduct the project was obtained from the review board of the College of Medicine, University of Kerbala. A four-month PtBL course was designed which was endorsed by the institute's curriculum committee. Twenty five year- four medical students and ten faculty members as course facilitators were included in the study. Five research teams were developed, and two faculty members supervised each team. Participation was voluntary, and informed consent was obtained from each participant. The research projects were designed to engage students in the screening of gestational diabetes and gestational hypertension. The project outcomes were assessed through post-tests, mini CEX, semi-structured feedback questionnaires, and focus group discussions. Quantitative data were statistically analyzed using SPSS, and the qualitative data were analyzed by thematic (content) analysis. Results: Most participants, 24 out of 25 students (98%) and all the faculty participants, expressed satisfaction with the contents and delivery of the course innovation. Ninety percent of the students reported significant improvement in their conceptual background and clinical and research-based skills. Although not statistically significant, students also reported improved teamwork, interpersonal and communication skills. In addition, the faculty members reported improvement in students' scientific engagement. Notably, all faculty recommended introducing PtBL in other areas of the medical curriculum. Conclusion: The initial results indicate that community research PtBL approach is an effective method to improve scientific engagement and active learning in medical students. Teams’ research results are being followed up to be harvested and analyzed to prove the longer term community health-related outcomes of this study. Carefully designed projects involving medical students can economically and effectively address public health problems. Therefore, medical educators might consider introducing a PtBL approach associated with discrete public health research goals early in the medical curriculum. Keywords Project-based learning; Students' engagement, Curriculum Innovation .